Decades of failure to prevent harm to patients—where are we going wrong? A mixed methods study of the perspectives of health services staff across Australia and internationally - Bierbaum, Mia; Yu, Yinghua; Molloy, Charlotte J.; Bowditch, Lorelle; Salmon, Paul M.; Middleton, Sandy; Braithwaite, Jeffrey; Hibbert, Peter (Frontiers in Health Services, 2025)
ContextPatient Safety Incident (PSI) reviews are undertaken frequently across health services in response to serious adverse events. This study investigated experiences and perceptions of healthcare professionals involved in incident review processes across four jurisdictions in Australia, alongside insights from international patient safety experts. These findings will inform the co-design of improvements to PSI reviews.MethodsSemi-structured interviews and focus groups were conducted, and participants completed an attitudinal and demographic survey. Inductive thematic analysis was conducted, and findings were deductively mapped against the Consolidated Framework for Implementation Research.FindingsAustralian (n = 99) and international (n = 11) participants took part in one of 25 focus groups (n = 78) or 32 interviews. Most participants (n = 99) completed the survey. Nearly all survey participants agreed/strongly agreed that PSI reviews are valuable for improving patient safety (95%), particularly when human factors and contextual influences on performance (76%) are considered. Two-thirds of participants agreed that investigations help prevent PSI recurrence (68%), avoid unfair blame (67%), and support continuous improvement (61%). However, fewer participants felt recommendations are consistently accepted by organisations (58%) or are appropriately targeted within the healthcare system (57%). Key strengths and challenges of the PSI review process were identified across three themes: Selection of PSI Reviews; Reviews, Recommendations and Implementation; and Health Organisations and Wider System Influences. Key PSI review challenges included: limited capacity and engagement, high staff workloads, turnover, and burnout, as well as variable skills, and limited human factors and systems thinking experience across review teams. Despite strong efforts to reduce a punitive culture, resistance to reporting and blame persists across some hospitals. Participants highlighted a learned powerlessness when developing systems thinking-based recommendations, resulting in the development of weaker, less resource intensive recommendations. Limited sharing of learnings and feedback on review findings, and variable monitoring, evaluation and accountability of recommendation implementation were also common challenges.ConclusionsThese findings have identified a need for system re-engineering of PSI reviews to address identified challenges and will inform the development of Best Practice Principles and a codesign of patient safety tactics for trial in-situ.